NIMG-49. A PROSPECTIVE, MULTI-CENTRE TRIAL OF FET-PET IN GLIOBLASTOMA PATIENTS - THE TROG 18.06 FIG STUDY: KEY ASPECTS OF IMAGING AND RADIATION ONCOLOGY CREDENTIALING. (12th November 2021) - Koh, Eng-Siew; Francis, Roslyn J; Ebert, Martin; Gan, Hui; Lee, Sze Ting; Lau, Eddie; Moore, Alisha; Grose, Andrew; Rossi, Alana; Ng, Sweet Ping; Yap, June; Ly, Tam; et al.
Abstract: The FIG study is a prospective non-randomised study now recruiting up to 210 newly diagnosed GBM participants across ten Australian sites. Study outcomes will address the role of [18F] fluoroethyl-L-tyrosine positron emission tomography (FET-PET) in radiotherapy (RT) planning, evaluation of post-treatment changes versus disease progression and prognostication. We describe here the methodology and preliminary outcomes for site credentialing. Eligible participants with GBM undergo FET-PET imaging at three time-points: FET-PET1-post-operative pre-chemo-RT, FET-PET2 acquired one month post-chemo-RT and FET-PET3 (+/-FDG-PET) triggered when clinical and/or radiological (MRI) progression is suspected. Dynamic and static FET-PET images are analysed qualitatively and quantitatively. Radiotherapy is as per standard care with the treating Radiation Oncologist (RO) blinded to FET-PET1. Site nuclear medicine (NM) physicians are required to delineate a biological target volume (BTV) based on FET-PET1 with hybrid RT volumes derived post-hoc. Pre-trial NM quality assurance comprises certification from the Australasian Radiopharmaceutical Trials Network encompassing FET-PET radiochemistry Quality Control and PET camera calibration. Site and central integrated workflows incorporating multi-modality image registration, target volume/region of interest contouring and analysis have been developed. NM benchmarking involves delineation of FET-PET BTVs in 3 cases with another 3 cases addressing response criteria interpretation harmonized across FET-PET, FDG-PET and MRI. Site ROs complete 3 cases involving standard and hybrid target volume delineation based on pre-derived FET-PET volumes. All NM and RO credentialing cases undergo central expert review. To date, of six sites which have submitted full credentialing data, 19/21 RO and 6/6 planning cases were passed. Of 72 NM cases, 18/72 (25%) required resubmission, primarily related to ensuring standardisation of background regions and time activity curve interpretation. The FIG study will be pivotal in establishing the role of FET-PET in GBM management. The robust NM and RO credentialing program will build capacity and expertise in FET-PET production, acquisition and image interpretation.